Estudio de factibilidad para la implementación de una unidad médica ambulante, en el GAD municipal del cantón Valencia, año 2014 - Cerda Velásquez, Adrián Ricardo (2015)
His research is entitled "" Feasibility study for the implementation of a mobile medical unit in the municipal GAD Canton Valencia, 2014 "whose aim is the implementation of a mobile medical unit in the municipal GAD Canton Valencia, who will attend the inhabitants of the canton, as a priority, taking preventive and hospital care. Among the objectives we have; theoretical foundation and a feasibility study stages, the evaluation of a feasible project, hospital, medical units, identify the level of acceptance that will implement the Mobile Medical Unit by market research, establish the technical functioning in at the implementation of the Mobile Medical Unit to allow its implementation, demonstrate the economic and financial convenience. The methods used in the study were; deductive, inductive, statistical and synthetic, while rates were constituted by; descriptive, and literature, in terms of research techniques were constituted by the surveys and interviews. During the process of scientific research, legal and theoretical several authors refer to the main subject data were obtained regarding the market study conducted resulted in 100% of respondents would use to other mobile medical unit. The technical study shows variables and main characteristics required for the project to make it as size and engineering, marketing strategies, logo, price, service sectors, promotion, advertising, supply and demand of the service to be provided. In the financial study it was determined an investment of $ 96611.48, while users who will serve in the five years will grow in so the project is feasible to ensure the health of a productive citizenship with a culture of prevention.